Hubungan Perilaku Caring Perwat dengan Tingkat Kepuasan Pasien - Mastur, Vergeina Ayu Mandalike; Megawe, Jenica Blandina (JURNAL ILMIAH KESEHATAN MANADO, 2025)
Nurses who provide nursing care with a poor caring attitude will give dissatisfaction to patients so that the quality of services in a hospital also decreases. Decreased satisfaction in the inpatient room can occur because nurses are less friendly and polite and nurses do not spend special time communicating with patients. The research used in this study is descriptive correlation, that is, the research with the research design is a cross sectional method. The sampling technique in this study is to use total sampling where the number of samples is equal to the number of population, which is 43 samples. The results were seen from 43 patients who assessed that nurses had behaved caring which were categorized as good, there were 21 patients, the category was quite good, there were 13 patients and those who said nurses were not good in caring behavior were 9 patients, so that from these results it was stated that the caring behavior of nurses was said to be good as seen from the results at Manado Medical Center Hospital. The test result was p=0.035 or a p value of < α (0.05), so there was a relationship between caring nurses and patient satisfaction in the hospital, so it was decided that Ha was accepted and Ho was rejected. The conclusion of the results of this study is that the caring behavior of nurses is the main factor in services in hospitals. Because patient satisfaction will be good if nurses are able to implement caring behavior well. It is hoped that the results of this research can add insight and become input and learning material in the field of nursing.